Grinding performance by applying MQL technique: an approach of the wheel cleaning jet compared with wheel cleaning Teflon and Alumina block - Ribeiro, Fernando Sabino Fonteque [UNESP]; Lopes, Jose Claudio [UNESP]; Garcia, Mateus Vinicius [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Mello, Hamilton Jose de [UNESP]; Aguiar, Paulo Roberto de [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
Characterized by the high heat generation, grinding has great difficulty in dry machining. As an alternative, it is proposed to apply abundant cutting fluid (conventional method) or a minimum amount of lubrication, which in turn dispenses with disposal costs and drastically reduces the volume of cutting fluid application during machining compared with the conventional technique. Despite this, the application of cutting fluids in MQL can cause clogging of the grinding wheel, damaging the workpiece quality. Against this, one of the techniques explored in the literature is the application of grinding wheel cleaning jet (WCJ), removing part of the layer adhered to the surface of the grinding wheel. Also, the present work proposes the cleaning of the cutting surface of the grinding wheel through the mechanical contact between Alumina (WCAB), and Teflon (WCTB) blocks with the cutting surface of the CBN grinding wheel, during cylindrical grinding of AISI 4340 steel hardened. Feed rates of 0.25; 0.50; 0.75, and 1 mm/min were applied under the following lubri-refrigeration conditions: conventional, MQL, and MQL with WCJ, WCAB, and WCTB. The parameters studied were roughness, roundness deviation, diametrical wheel wear, grinding power, acoustic emission, and microstructural analysis. The results showed that the WCAB and WCTB could improve grinding conditions compared with MQL without cleaning, mainly when applied with Alumina block. However, WCJ is the better condition associated with MQL. However, the conventional flood lubricant application remains with better results, indicant that it is necessary more effort to improve the MQL technique.
Keywords: External cylindrical grinding; Wheel cleaning jet; Wheel cleaning Alumina block; Wheel cleaning Teflon block; Mechanical cleaning; Hardened steel AISI 4340